Teacher perceptions of student metacognition in project-based learning contexts before and after professional development - McKendree, Robert B. (Kansas State University, 2019)
This qualitative study investigated how six secondary school teachers facilitated learning and perceived metacognition in a Project-based Learning (PBL) instructional environment after participating in professional development (PD) on metacognitive strategies. Using symbolic interactionism as the philosophical overview, and following the Seidman interviewing technique, each participant was interviewed three times at different stages of the Guskey model of teacher change: before the metacognitive PD, after the metacognitive PD, and after implementing a PBL curriculum with metacognitive strategies. The participants included teachers who had previously completed trainings on the Food and Nutritional Sciences (FNS) PBL curriculum. Four questions guided this study: (a) how does knowledge of metacognitive strategies influence teacher perception of the learning process in a PBL instructional environment; (b) how do teachers facilitate student learning in a PBL instructional environment before and after metacognitive professional development; (c) what are educators’ interpretations of student metacognitive regulation and knowledge during a PBL instructional environment; and (d) how do teachers view their roles in influencing student metacognition? Findings are presented, including before participating in the metacognitive PD teacher-participants described the learning process as emphasizing the need for engagement, relevancy, and discovery. Additionally, their discussions often focused on the teacher as accountable for students’ learning. When discussing PBL and the learning process, teacher-participants indicated PBL engages students, fosters accountability both though internal and external forces, promotes learning other than just rote memorization, and offers the opportunity to help struggling students. Teacher-participant interviews after the metacognitive PD suggest teacher-participants were eager to implement new metacognitive facilitation strategies developed during the metacognitive PD. However, several factors precluded some teacher-participants from fully implementing the PBL curriculum and metacognitive strategies, including decreasing self-efficacy toward facilitating metacognition, confounding conceptualizations of metacognition and PBL, and time constraints. A key finding from post-PD interviews is metacognition seemed to be a complex PD topic that challenged teacher-participant paradigms toward teaching and learning, suggesting further PD and reinforcement might be warranted as teachers grapple with how metacognition meshes with their previous learning paradigms. Additionally, at the conclusion of the study teacher-participants still perceived value in facilitating metacognition within their students, and a desire for further training in metacognitive facilitation. Implications for practice are also presented, including the possible need for a more cyclical model for PD focusing on complex topics. A revised model for PD on complex topics is proposed, offering PD participants opportunities to implement new practices, and then further refine conceptualizations, before potentially adjusting their beliefs about teaching and learning. Further, implications for practice include increasing PD focused on metacognition, as well as incorporating metacognition into preservice teacher education programs. Lastly, suggestions for future research include examining the structure of metacognitive PD, exploring the most effective PD methods for metacognition, and inquiries into metacognition instruction in preservice teacher education.
Keywords: Metacognition; Project-based learning